Digital Asset Management ROI - Davey, Mark (Henry Stewart Talks, 2010)
ROI as it relates to DAM, Types of DAM, What is ROI?, Document management, Audio of the future, Content marketing, Rich media, Brand control, Metadata, The importance of the information, Knowledge management (KM), Trends, Common mistakes, Recommendations